UJI MULTIKOLINEARITAS: PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PENGURANGAN TINGKAT PENGANGGURAN DI KAB. SIDOARJO - Rahma, Dilla Nur; Kumala Dewi, Refita Ayu; widya nanda, Angelika gladys (Jurnal Edukasi Ekonomi, 2023)
Economic growth is an indicator of the success of economic development, characterized by the process of increasing output per capita in the long term. Efforts to accelerate regional development can be done by increasing economic growth. Efficiency in economic activities must be accompanied by adequate infrastructure, especially road and electricity infrastructure, so that it will encourage a sustainable increase in regional potential, where the development of infrastructure in Indonesia is currently progressing quite rapidly in Indonesia, both in national and regional infrastructure development. One of the areas that is developing rapidly in the infrastructure development process is Kab. Sidoarjo. District growth. Sidoarjo from 2010 to 2020 has not yet met the target in terms of development, there is still a lot of infrastructure that has not been improved, however, in the development of infrastructure development which will start in 2021, there will be a lot of development in infrastructure starting in the District. Sidoarjo, starting from road concreting to fulfilling public facilities carried out by the District Public Works and Spatial Planning Department. Sidoarjo. In infrastructure development in Kab. Sidoarjo can have a significant influence on economic growth which is used in economic growth and in infrastructure development, of course absorbing local energy which is used to fulfill work requirements in the district. Sidoarjo.